Oncogenic drivers in 11q13 associated with prognosis and response to therapy in advanced oropharyngeal carcinomas - Barros-Filho, M. C. (2018)
Objectives: To identify potential molecular drivers associated with prognosis and response to treatment in advanced oropharyngeal squamous cell carcinomas (OPSCC). Materials and methods: Thirty-three OPSCC biopsies from untreated Brazilian patients were evaluated for human papilloma virus genotyping, genome wide copy number alterations and gene expression profiling. Data were integrated using CONEXIC algorithm. Validation with TCGA dataset and confirmation by RT-qPCR of candidate genes were performed. Results: High-risk HPV positive cases, detected in 55% of advanced OPSCC, were associated with better outcome. Losses of 8p11.23-p11.22, 14q11.1-q11.2 and 15q11.2, and gains of 11q13.2 and 11q13.2-q13.3 were detected as recurrent alterations. Gains of 3q26.31 and 11q13.2 and losses of 9p21.3 were exclusively detected in HPV-negative tumors. Two clusters of expression profiles were observed, being one composed mostly by HPV positive cases (83%). HPV-positive enriched cluster showed predominantly immune response-related pathways. Integrative analysis identified 10 modulators mapped in 11q13, which were frequently cancer-related. These 10 genes showed copy number gains, overexpression and an association with worse survival, further validated by TCGA database analyses. Overexpression of four genes (ORAOV1, CPT1A, SHANK2 and PPFIA1) evaluated by RT-qPCR confirmed their association with poor survival. Multivariate analysis showed that PPFIA1 overexpression and HPV status are independent prognostic markers. Moreover, SHANK2 overexpression was significantly associated with incomplete response to treatment. Conclusion: The integrative genomic and transcriptomic data revealed potential driver genes mapped in 11q13 associated with worse prognosis and response to treatment, giving fundamentals for the identification of novel therapeutic targets in OPSCC.